From government to governance: School coalition for promoting educational quality and equity in China. Issue 2 (February 2022) - Huang, Zhongjing; Chen, HuanChun
The major aim of recent school education reform in China is to improve educational equity and quality. This paper aims to explore a collaborative reform in a school district in Hangzhou in Zhejiang Province. The major focus of the reform has been a change of school management from "government" to "governance, " which is a shift from individual school effort to multi-school collaboration, from a single point development to a regional ecological development, as well as from loose development to excellence and equality development. Under such reform and through the school coalition among all schools within the district, high-quality and balanced development of the regional education has been promoted. Reform strategies in the school coalition studied include enhancing educational equity within the coalition; coordinating multiple powers; upholding educational quality by a shared curriculum; putting in extra resources to release school burdens; improving the quality of the teaching force; and developing an evidence-based comprehensive assessment system. The results of such changes not only promote teacher professional development but also meet students' individual needs and growth. The schools involved in the collaborative endeavor have all earned support and recognition from parents, respect from the bureau, and a good reputation, and have improved competitiveness in Hangzhou.